1985
DOI: 10.1007/bf00391029
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of chilling-induced photooxidative damage to leaves of Cucumis sativus L. by treatment with amino alcohols

Abstract: The effect of pretreatment of cucumber (Cucumis sativus L.) roots with choline chloride or ethanolamine on leaf phospholipid composition and light-induced leaf damage during chilling was studied. Photooxidative chlorophyll degradation was similarly inhibited by both amino alcohols. The decrease of the chlorophyll a/chlorophyll b ratio and the increase of polyunsaturated-fatty-acid degradation during chilling in the light were equally inhibited by pretreatment with choline chloride or ethanolamine. Treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…The increased level of damage observed when cucumber seedlings are chilled in light instead of dark is consistent with previously reported results with cucumber leaf discs. Van Hasselt (19) demonstrated that chilling in light caused more damage than chilling in dark and in subsequent reports (6,20) indicated that injury was due to photo-oxidative degradation of leaf pigments, lipids, and fatty acids. Garber (4) also found that cucumber cotyledon discs were more severely damaged by chilling in light than in dark, resulting in loss of photosynthetic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The increased level of damage observed when cucumber seedlings are chilled in light instead of dark is consistent with previously reported results with cucumber leaf discs. Van Hasselt (19) demonstrated that chilling in light caused more damage than chilling in dark and in subsequent reports (6,20) indicated that injury was due to photo-oxidative degradation of leaf pigments, lipids, and fatty acids. Garber (4) also found that cucumber cotyledon discs were more severely damaged by chilling in light than in dark, resulting in loss of photosynthetic activity.…”
Section: Resultsmentioning
confidence: 99%
“…PC also appears to be the phospholipid preferentially degraded during low temperature stress in leaves of cucumber plants (5). Due to its membrane fluidizing properties (8) damaging membranes and proteins (24), and deesterifying membrane fatty acids (17). Lipid peroxidation also induces the molecular ordering of membranes with a concomitant loss in membrane semipermeability (24 (23).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase activities are known to be rapidly activated upon (14). A phospholipid fraction extracted with boiling isopropanol from excised discs of cucumber leaf tissue also had a percent PA content of about 4% (8). Therefore, for the present study, levels of PA above 4 to 5% are considered as increases taking place in the tissue during storage.…”
Section: Changes In Glycolipids and Phospholipidsmentioning
confidence: 95%
“…For example, in tobacco the direct effect of different in vitro culture conditions over the cellular lipid contents and ratios and in particular over PC biosynthesis has been demonstrated (Chervin et al, 1995). Abiotic stresses such as salt, cold, heat or mannitol also influence PC biosynthesis (Horvath and Vanhasselt, 1985;Kinney et al, 1987;Tasseva et al, 2004). Therefore, promotion of nuclear fusion during androgenic development could also be influenced by altered phospholipid ratios, in this case due to the in vitro environment.…”
Section: Looking For Cellular and Molecular Basis Of Nuclear Fusionmentioning
confidence: 99%